CORRELATION BETWEEN ORGANIZATIONAL CULTURE AND WORKING CLIMATE - Akram Akram (Universitas Negeri Malang, 2021)
Abstract: This study aims to: 1)describe the reality of organizational culture; 2)describe the reality of the work climate, and 3)examine the correlation between organizational culture and work climate at Madrasah Tsanawiyah(Islamic Middle School) 1 Bone South Sulawesi. This research uses a quantitative methodology with a correlational design to explain the research questions. The instrument used to measure the variables of this study was a questionnaire then analyzed with descriptive statistics and inferential statistics use analysis of the product-moment with SPSS version 25 software. The result of the study show in descriptive of organizational culture is in the very conducive category of 86,38% and work climate is in the conducive category of 81,09%. In addition, the analysis of inferential with correlation product moment analysis suggests that there is a positive and significant correlation between organizational culture and work climate, signified by a correlation coefficient of 51,4%, which is a mid-level of correlation. With the organizational culture at MTSN 1 Bone in the form of values and norms that have a positive impact on the creation of a conducive work climate. Keywords: The Organization; Organizational Culture; Work Climate